Exploring the anti-inflammatory effects of phytochemicals in attenuating interstitial cystitis-a literature review - Anjum, Irfan; Nasir, Ayesha; Naseer, Faiza; Ibrahim, Ahsan; Rehman, Bisma; Bashir, Fawad; Tul Ain, Qura (Frontiers in Pharmacology, 2025)
Interstitial cystitis is a fierce syndrome affecting the quality of life of thousands of individuals around the globe. It causes immense pain in the bladder and associated viscera along with inflammation-like lesions. The current medicinal and pharmacological research focuses on the protective and curative effects of phytochemicals in several ailments. Phytochemicals derived from many medicinal plants have shown potent outcomes in protection against various pathological conditions including interstitial cystitis. This review has summarized the insights of in vitro and in vivo studies regarding the effects of phytochemicals in fading the inflammation in bladder tissue and exhibiting a protective effect on the urothelium. Hemorrhagic cystitis is a common manifestation in patients undergoing chemotherapy with cyclophosphamide and related alkylating agents. Sodium 2-mercaptoethane sulfonate (Mesna) has traditionally been employed in clinical practice to counter cyclophosphamide-induced cystitis in humans. However, cyclophosphamide has been employed in developing animal models of interstitial cystitis in in vivo studies. Phytochemicals including quercetin, beta-caryophyllene, curcumol, boswellic acid, caftaric acid, some flavonoids and other secondary metabolites being a consequential component of numerous medicinal plants, have displayed a significant reduction in the levels of proinflammatory cytokines including TNF-α, NFĸB, IL-1β, NLRP3 inflammasome, IL-6, IL-2, matrix metalloproteinases etc. Uroprotective outcomes of these phytochemicals have been found to result in diminished oxidative stress and restoration of glutathione, superoxide dismutase, and related proteins in the inflamed bladder tissue. Many in vivo studies involving cyclophosphamide-induced interstitial cystitis have confirmed these findings. The coupling of phytotherapy with novel drug delivery systems such as nanoparticles, liposomes, nanotubes, quantum dots, etc. can help translate these beneficial effects of phytochemicals into clinical practice. Further investigations of these phytochemicals can provide intuition regarding the development of newer drug molecules having exclusive activity for attenuating interstitial cystitis.